2021
DOI: 10.3390/cancers13133313
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Deep-Learning Pipeline to Recognize and Characterize Macrophages in Colo-Rectal Liver Metastasis

Abstract: Quantitative analysis of Tumor Microenvironment (TME) provides prognostic and predictive information in several human cancers but, with few exceptions, it is not performed in daily clinical practice since it is extremely time-consuming. We recently showed that the morphology of Tumor Associated Macrophages (TAMs) correlates with outcome in patients with Colo-Rectal Liver Metastases (CLM). However, as for other TME components, recognizing and characterizing hundreds of TAMs in a single histopathological slide i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Deep learning techniques demonstrate considerable bene ts in terms of precision and e ciency, due to the signi cant variations in the morphological characteristics of macrophages. The deep-learning pipeline, which is based on the innovative DeepLab-v3 architecture and semantic segmentation technique proposed by Cancian a et al [24], effectively enables the isolation of tumor-associated macrophages (TAMs) from the background and facilitates the identi cation of individual TAMs. Ong et al [11] compared the accuracy and speed of the model, which was developed using YOLOv5, to the current standards such as the Watershed/Gaussian mixture model (GMM) method and Cellpose technique in the context of macrophage cell detection during drug activity investigation.…”
Section: Macrophage Segmentationmentioning
confidence: 99%
“…Deep learning techniques demonstrate considerable bene ts in terms of precision and e ciency, due to the signi cant variations in the morphological characteristics of macrophages. The deep-learning pipeline, which is based on the innovative DeepLab-v3 architecture and semantic segmentation technique proposed by Cancian a et al [24], effectively enables the isolation of tumor-associated macrophages (TAMs) from the background and facilitates the identi cation of individual TAMs. Ong et al [11] compared the accuracy and speed of the model, which was developed using YOLOv5, to the current standards such as the Watershed/Gaussian mixture model (GMM) method and Cellpose technique in the context of macrophage cell detection during drug activity investigation.…”
Section: Macrophage Segmentationmentioning
confidence: 99%
“…No studies used prospectively collected data. The algorithms primary goal was either segmentation (6/22) [11][12][13][14][15][16], classification (6/22) [17][18][19][20][21][22] or prediction (10/22) [23][24][25][26][27][28][29][30][31][32]. The majority of studies (18/22) were focused on hepatocellular carcinoma.…”
Section: Tumoralmentioning
confidence: 99%
“…By examining the available related literature, only two studies were found. In one study, Cancian P et al [ 101 ] attempted to employ a deep-learning pipeline to characterize TAMs in colorectal cancer liver metastasis. Through their comparisons, the authors found that AI can totally and successfully recognize TAMs embedded in the tumor microenvironment.…”
Section: Artificial Intelligence (Ai) and Tamsmentioning
confidence: 99%